Women and the Second World War in France, 1939-1948 : choices and constraints - Diamond, Hanna, 1 (Longman, 1999., 1999)
Hanna Diamond presents varied testimony to reveal the realities of women's daily lives and the role they played in both collaboration and resistance. She considers the political choices they had to make and the constraints they were under.